(untitled) (CIPEEX, 2025)
Contemporary democracy is based on the realization of free, secure, and transparent elections, with the Brazilian electoral process standing out internationally since the adoption of electronic voting machines in 1996. This study, of a qualitative and exploratory bibliographic nature, critically analyzes the use of technology in elections, drawing on academic, institutional, and legal documents, especially those produced by the Superior Electoral Court. The results indicate that electoral computerization has provided remarkable advances in efficiency, security, and transparency, significantly reducing the vote-counting time and strengthening the credibility of decisions. The introduction of mechanisms such as biometric identification and the polling station report contributed to reducing fraud and expanded oversight by political parties and civil society. Another relevant aspect is transparency, achieved through the disclosure of source codes and the possibility of external audits, enabling the participation of experts and social organizations in monitoring the process, an essential factor in building public trust. However, significant challenges remain, especially related to cybersecurity and the spread of disinformation. Attempts at digital attacks, even if they have not compromised the integrity of the system, reveal vulnerabilities inherent to computerized environments. The proliferation of false news, in turn, fuels distrust and directly affects electoral legitimacy. Moreover, logistical failures and occasional delays highlight the need for constant improvement in the training of staff and operational planning. In this context, the Brazilian model presents itself as a relevant case study for other democracies seeking to adopt or modernize electronic voting systems, by combining technological innovation, institutional rigor, and mechanisms of social participation. It is concluded that the computerized electoral process constitutes a significant democratic advance but requires continuous investments in technology, training, and public policies aimed at reducing emerging risks. The future of electronic voting in Brazil must balance innovation with caution, strengthening social trust and ensuring the legitimacy of the process.